Pengembangan Bioplastik Antibakteri Untuk Bahan AAlat Pelindung Diri (APD) yang Ramah Lingkungan - Dadang Suhendar; Ghina Eroz Rasman; Aji Sutrisno (Syntax Corporation Indonesia, 2021)
Production of Personal Protective Equipment (PPE) increased by 40% per month, resulting in global plastic waste during the pandemic and after the COVID-19 pandemic. Degradable plastic is a solution left over from PPE. This research uses environmentally friendly and non-toxic materials, namely PLA, chitosan, ZnO, and palm wax. There are two stages of research, (1) determining the best concentration of palm oil wax (1; 2.5; 5%) according to SNI, and (2) determining the concentration of chitosan (0.5%; 0.75%; 1%; 1, 25%; 1.5%) using the RAL method. Bioplastics were tested for morphology, structure, antibacterial, water vapor permeability, and biodegradability. The results of the morphological test showed cracks and crevices of chitosan in several places. The FTIR test confirmed that the addition of chitosan did not change the chemical components of the bioplastic. Chitosan concentration of 0.5% was the best in inhibiting Staphylococcus aureus and Escherichia coli bacteria. The addition of chitosan made the tensile strength value increase but decreased elongation at rest, the WVP test had no significant effect, while the biodegradability test at the smallest concentration of chitosan could increase the biodegradability.